The participatory development and implementation of a facilitator's manual for the promotion of exclusive breastfeeding - Katsinde, Shingirai Miranda (Rhodes University, Faculty of Pharmacy, Pharmacy, 2016)
Background: Breastfeeding is a common practice, but exclusive breastfeeding for the first six months is no longer a cultural norm in the majority of South African communities. Identification of facilitating and constraining factors which affect breastfeeding and exclusive breastfeeding practices is thus important. The promotion of exclusive breastfeeding is essential for improved infant health and development, especially if it takes into consideration the broader cultural and socio-economic aspects influencing these practices. This study follows up on an initial project conducted in Glenmore and Ndwayana, two rural communities in the Eastern Cape, South Africa. The current study aimed at working with community care workers who are associated with two community based organisations, who work within three communities, Glenmore, Ndwayana and Grahamstown. The study objectives were to identify the factors that influence the adoption of exclusive breastfeeding in the communities researched, to conduct workshops with the community workers on exclusive breastfeeding practices, as well as to develop and implement a facilitator's manual for the promotion of exclusive breastfeeding. Method: Using the community based participatory research approach and the PEN-3 theoretical framework to guide the research process, individual semi-structured interviews were conducted with 14 community care workers to identify the factors that affect breastfeeding and exclusive breastfeeding. Through participatory involvement and a cyclical research process, a facilitator's manual on breastfeeding was developed, which was used during the workshops in the training of community care workers on breastfeeding and exclusive breastfeeding practices. A pre and post intervention knowledge questionnaire was given to the community care workers to complete before and after the workshops. The facilitator's manual was modified based on 14 months of consistent interaction with the community care workers, who provided feedback on improving the content as well as on how to enhance the cultural appropriateness of the facilitator's manual during guided focus group discussions. Readability testing also guided further modification of the facilitator's manual. Results:The major findings confirmed that exclusive breastfeeding for six months was no longer a common practice in these three communities. Factors affecting breastfeeding and exclusive breastfeeding were classified as perceptions (knowledge attitudes and beliefs), enablers (resources and facilities) and nurturers (people), in accordance with the PEN-3 model thematic categories. The knowledge questionnaire, semi-structured interview results, and data from the workshops showed that the community care workers were not sufficiently equipped with information on breastfeeding and exclusive breastfeeding. The facilitator's manual development and modification was made possible by inputs from the community care workers and the community based organisation liaisons. A culturally appropriate, community specific facilitator's manual for the promotion of breastfeeding and exclusive breastfeeding was produced. Conclusion: The factors affecting breastfeeding and exclusive breastfeeding were identified. These factors were useful in facilitating discussions on how to improve breastfeeding and exclusive breastfeeding practices in the communities researched. The facilitator's manual and the workshops were useful in equipping community care workers with knowledge on breastfeeding and exclusive breastfeeding. The involvement of community based organisations will assist to ensure sustainability of breastfeeding promotion by community care workers by adopting the facilitator's manual as part of their women and child development programmes.
Keywords: Uncatalogued